Thermodynamic Correlation between Liquid-Liquid Phase Separation and Crystalline Solubility of Drug-Like Molecules - Taiga Uekusa; Tomohiro Watanabe; Daiju Watanabe; Kiyohiko Sugano (MDPI AG, 2022)
The purpose of the present study was to experimentally confirm the thermodynamic correlation between the intrinsic liquid-liquid phase separation (LLPS) concentration (<semantics><msubsup>S0LLPS</msubsup></semantics>) and crystalline solubility (<semantics><msubsup>S0c</msubsup></semantics>) of drug-like molecules. Based on the thermodynamic principles, the crystalline solubility LLPS concentration melting point (<semantics>Tm</semantics>) equation (CLME) was derived (<semantics>log10<msubsup>S0C</msubsup>=log10<msubsup>S0LLPS</msubsup>−0.0095<mfenced>Tm−310</mfenced></semantics> for 310 K). The <semantics><msubsup>S0LLPS</msubsup></semantics> values of 31 drugs were newly measured by simple bulk phase pH-shift or solvent-shift precipitation tests coupled with laser-assisted visual turbidity detection. To ensure the precipitant was not made crystalline at <10 s, the precipitation tests were also performed under the polarized light microscope. The calculated and observed <semantics>log10<msubsup>S0C</msubsup></semantics> values showed a good correlation (root mean squared error: 0.40 log unit, absolute average error: 0.32 log unit).